2018
DOI: 10.1111/trf.14797
|View full text |Cite
|
Sign up to set email alerts
|

Our experience in riboflavin and ultraviolet light pathogen reduction technology for platelets: from platelet production to patient care

Abstract: Although PRT can improve PLT safety, it can increase the amount of PLTs required for transfusion in some patient categories. The cost of PRT can be partially offset by the savings associated with a lower rate of PLT outdates. This cost reduction can be a key factor in settings where inventory management is challenged by a high percentage of wasted PLTs due to outdating.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…Our comparative study shows that neonates transfused with PLTs diluted in PAS and treated with riboflavin and UV light‐PRT require the transfusion of more PLTs than neonates receiving standard PLTs. Additionally, the adverse transfusion reaction rate in children transfused with PAS‐PLTs treated with riboflavin and UV light was found to be in accordance with data in the literature for children and adults receiving PLTs treated with the same PRT. PRT‐treated PLTs seem to be safe for children, since in 5 years (2013‐2017) not a single severe PLT transfusion reaction was reported in children transfused with riboflavin and UV light‐treated PLTs.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Our comparative study shows that neonates transfused with PLTs diluted in PAS and treated with riboflavin and UV light‐PRT require the transfusion of more PLTs than neonates receiving standard PLTs. Additionally, the adverse transfusion reaction rate in children transfused with PAS‐PLTs treated with riboflavin and UV light was found to be in accordance with data in the literature for children and adults receiving PLTs treated with the same PRT. PRT‐treated PLTs seem to be safe for children, since in 5 years (2013‐2017) not a single severe PLT transfusion reaction was reported in children transfused with riboflavin and UV light‐treated PLTs.…”
Section: Discussionsupporting
confidence: 87%
“…Therefore, riboflavin and UV light PRT together with PLT storage in PAS can apparently reduce the rate of febrile and allergic reactions to PLT transfusions in children. Our group has recently demonstrated that the transfusion of PAS‐PLTs treated with riboflavin and UV light significantly decreases the rate of febrile and allergic transfusion reactions in adults . Furthermore, all PLT transfusion reactions observed in children were mild from 2013‐2017.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…A number of reports describe local and national programmes developed during the voluntary or mandatory implementation of platelet PRT in different geographical regions (Osselaer et al , ; Jimenez‐Marco et al , , ; Jutzi et al , ; Garraud & Lozano, ; Rutter & Snyder, ) and the outcomes of regular haemovigilance programmes developed after routine PRT use (Knutson et al , ; Łętowska et al , ; Piotrowski et al , ).…”
Section: Management and Cost Of Pathogen Reduction Technologiesmentioning
confidence: 99%